PENGARUH PEMASANGAN RAMBU-RAMBU JALUR EVAKUASI TERHADAP WAKTU REAKSI TANGGAP DARURAT BAHAYA KEBAKARAN DI PERUSAHAAN X SEMARANG - Hidayat, Muhammad Taufik; Widjasena, Baju; Wahyuni, Ida (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT Fire is very unintended thing in the company. It can emerge affliction and catastrophic for employees, particularly for those who encounter the accident and can lose the job although they are safe. Evacuation signs (evacuation mediums) are very important as the effort of preventing fire for every company and casualties in particular. The absence of evacuation signs in the ?X? company Semarang can emerge the casualties when the fire is happening. The aim of this research was designed to find out the evacuation efficiency differences between before and after the fire evacuation signs application in the x company Semarang. The research employed Quasi Experiment with Control Group Pretest and Postest Design. There were 4 steps in this research the first day of counting time before instalation evacuation rute signs, the scondary and third day of the instalation evacuation route signs, the fourt day to be giving instruction on installing the sample evacuation roiute signs, day of the fifth and sixth sample with signs of adaption seventh day of the evacuation route and evacuation time calculation done after the installation of evacuation route signs, followed by a disscusion group of samples. The collected data examined by using paired t-test. The result was founded that there were differences of evacuation efficiency average i.e. the average with 3.95  before the application and 2.26 minutes after the application. The result also showed that there were significant differences by using paired t-test experiment i.e. before and after with 0.000 or less than 0.05 (p<0.05). It can be concluded that there were differences of evacuation efficiency between before and after the application of fire evacuation signs. Kata Kunci :  waktu evakuasi, alarm, api  Kesmasindo Volume 4(1,)Januari 2011, hlm. 72-80